2020
DOI: 10.1002/jcp.29727
|View full text |Cite
|
Sign up to set email alerts
|

SIRT3 deficiency is resistant to autophagy‐dependent ferroptosis by inhibiting the AMPK/mTOR pathway and promoting GPX4 levels

Abstract: Ferroptosis, an autophagy‐dependent cell death, is characterized by lipid peroxidation and iron accumulation, closely associated with pathogenesis of gestational diabetes mellitus (GDM). Sirtuin 3 (SIRT3) has positive regulation on phosphorylation of activated protein kinase (AMPK), related to maintenance of cellular redox homeostasis. However, whether SIRT3 can confer autophagy by activating the AMPK‐mTOR pathway and consequently promote induction of ferroptosis is unknown. We used human trophoblastic cell li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
112
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 164 publications
(115 citation statements)
references
References 47 publications
3
112
0
Order By: Relevance
“…A recent study showed that glucose depletion prevents ferroptosis caused by erastin and RSL3 in immortalized mouse embryonic fibroblasts (MEFs) by activating AMP-activated protein kinase (AMPK)-mediated phosphorylation of acetyl-CoA carboxylase (Lee et al, 2020). In contrast, AMPK-mediated phosphorylation of Beclin 1 promotes ferroptotic cell death in colon cancer cells (e.g., PANC1; Song et al, 2018a) and noncancer cells (e.g., HTR8/Svneo; Han et al, 2020)). Moreover, AMPK-mediated stearoyl-CoA desaturase (SCD/SCD1) downregulation promotes ferroptosis in hepatocellular carcinoma cells by inhibiting production of monounsaturated fatty acids (MUFAs) (Zhao et al, 2020).…”
Section: Figure 2 Pyruvate Oxidation-dependent Fatty Acid Synthesis Facilitates Ferroptosismentioning
confidence: 99%
“…A recent study showed that glucose depletion prevents ferroptosis caused by erastin and RSL3 in immortalized mouse embryonic fibroblasts (MEFs) by activating AMP-activated protein kinase (AMPK)-mediated phosphorylation of acetyl-CoA carboxylase (Lee et al, 2020). In contrast, AMPK-mediated phosphorylation of Beclin 1 promotes ferroptotic cell death in colon cancer cells (e.g., PANC1; Song et al, 2018a) and noncancer cells (e.g., HTR8/Svneo; Han et al, 2020)). Moreover, AMPK-mediated stearoyl-CoA desaturase (SCD/SCD1) downregulation promotes ferroptosis in hepatocellular carcinoma cells by inhibiting production of monounsaturated fatty acids (MUFAs) (Zhao et al, 2020).…”
Section: Figure 2 Pyruvate Oxidation-dependent Fatty Acid Synthesis Facilitates Ferroptosismentioning
confidence: 99%
“…By contrast, Zhao et al established that excessive autophagy in H9c2 cells was induced in a HG medium 26 . Furthermore, two studies reported that high concentrations of glucose facilitated autophagy activation in trophoblast cell lines and the cardiomyocyte cell lines 27 , 28 . To the best of our knowledge, the effects of HG on autophagy in chondrocytes remain indeterminate.…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is abnormally high in tumour cells, which is assumed to be closely related to the abnormally active cell division and metabolism [28][29][30][31]. However, many recent studies have demonstrated that autophagy and ferroptosis are not two independent events but are inextricably linked [31][32][33][34][35]. Autophagy and ferroptosis are mutually reinforcing and interdependent, and they exhibit different interrelationships in different individuals, cells, and disease processes [33,34].…”
Section: Discussionmentioning
confidence: 99%